Citation Behavior of Advanced Undergraduate Students in the Social Sciences: A Mixed-Method Approach. Issue 2 (2nd April 2016) - Datig, Ilka
ABSTRACT: Citation analysis is a popular research method in library science, often used to evaluate collections and instructional services. There are multiple advantages to combining citation analysis with qualitative research methods. This article describes a study in which Capstone projects by graduating undergraduate students in the social sciences were examined using both citation analysis and focus groups. The goal of this research was to gain a greater understanding of the types of sources used by advanced undergraduates in the social sciences, the library-provided availability of those sources, and a sense of how these students find, evaluate, and select sources for their Capstone projects. Notable findings include the heavy reliance of students on journal articles and the large influence of professors and other mentors on students' citation behavior.